INSTITUTIONAL DECENTRALIZATION AND WATER MANAGEMENT UNDER THE LEGAL APPROACH: THE RIO DAS VELHASWATERSHED CASE, MG, BRAZIL - Theodoro, H. D.; Nascimento, N. de O.; Heller, L. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The research focuses on the study of the institutional management of water resources from the perspective of the legal approach as the model of participatory governance, legal proposed decentralized and integrated in the country has problems and analytical evaluation constant demand. For both the object of study is the Rio das Velhas Watershed Committee, located in Minas Gerais, Brazil, one of the oldest in this state, also pioneer in use of various bureaucratic and legal mechanisms for water management. The goal is to identify the main constraints and potential for a watershed committee can act currently in the existing Brazilian institutional and legal framework. This is accomplished by the use of "triangulation of methods" qualitative research (documents, participant observation and content analysis of interviews with leaders from the water sector). The results indicate that there is a gap between theory and practice of public management of water resources, and the maintenance of various power and decision-making asymmetries. The conclusion is that the institutional and social interactions are essential to the legal dimension be well applied in water resources management system.